The first letter position effect in visual word recognition: The role of spatial attention. - Aschenbrenner, Andrew J.; Balota, David A.; Weigand, Alexandra J.; Scaltritti, Michele; Besner, Derek (Journal of Experimental Psychology. Human Perception & Performance, 2017)
A prominent question in visual word recognition is whether letters within a word are processed in parallel or in a left to right sequence. Although most contemporary models posit parallel processing, this notion seems at odds with well-established serial position effects in word identification that indicate preferential processing for the initial letter. The present study reports 4 experiments designed to further probe the locus of the first position processing advantage. The paradigm involved masked target words presented for short durations and required participants to subsequently select from 2 alternatives, 1 which was identical to the target and 1 that differed by a single letter. Experiment 1 manipulated the case between the target and the alternatives to ensure that previous evidence for a first position effect was not due to simple perceptual matching. The results continued to yield a robust first position advantage. Experiment 2 attempted to eliminate postperceptual decision processes as the explanatory mechanism by presenting single letters as targets and requiring participants to select an entire word that contained the target letter at different positions. Here the first position advantage was eliminated, suggesting postperceptual decision processes do not underlie the effect. The final 2 experiments presented masked stimuli either all vertically (Experiment 3) or randomly intermixed vertical and horizontal orientation (Experiment 4). In both cases, a robust first position advantage was still obtained. The authors consider alternative interpretations of this effect and suggest that these results are consistent with a rapid deployment of spatial attention to the beginning of a target string which occurs poststimulus onset.